2020
DOI: 10.1007/978-3-030-44651-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Berger-Coburn Theorem, Localized Operators, and the Toeplitz Algebra

Abstract: We consider various classes of bounded operators on the Fock space F 2 of Gaussian square integrable entire functions over the complex plane. These include Toeplitz (type) operators, weighted composition operators, singular integral operators, Volterra-type operators and Hausdorff operators and range from classical objects in harmonic analysis to more recently introduced classes. As a leading problem and closely linked to well-known compactness characterizations we pursue the question of when these operators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…So if T was band-dominated, then T restricted to F 2 1 would be compact by Theorem 16, which it obviously is not. Further, maybe more interesting examples are provided in [5,Example 2], for instance.…”
Section: Compact Toeplitz and Hankel Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…So if T was band-dominated, then T restricted to F 2 1 would be compact by Theorem 16, which it obviously is not. Further, maybe more interesting examples are provided in [5,Example 2], for instance.…”
Section: Compact Toeplitz and Hankel Operatorsmentioning
confidence: 99%
“…We have seen in Corollary 6 that every Toeplitz operator with bounded symbol is banddominated. Bauer and Fulsche [5] showed that the algebra of band-dominated operators on F 2 is generated by Toeplitz operators. A natural question is therefore: Question 33.…”
Section: Remarks and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corollary 7.12 provides us a tool to study the C*-algebra VT generated by Toeplitz operators with translation-invariant generating symbols. A natural problem is to find the C*-algebra generated by all Toeplitz operators with bounded symbols (not necesarily translation-invariant), acting in a RKHS H. Various characterizations of this Toeplitz algebra have been found for the Bergman and Segal-Bargmann-Fock spaces, see Xia [38], Bauer and Fulsche [4], and Hagger [17]. Much earlier, Engliš [8] proved that Toeplitz operators acting in the Bergman space L 2 hol (D) are weakly dense in B(L 2 hol (D)).…”
Section: Spectral Functions Of Toeplitz Operators With Translation-in...mentioning
confidence: 99%
“…Hachadi and Youssfi [14] developed a general scheme for computing the reproducing kernels of the spaces of polyanalytic functions on radial plane domains (disks or the whole plane) with radial measures. There are general investigations about bounded linear operators in reproducing kernel Hilbert spaces (RKHS), especially about Toeplitz operators in Bergman or Fock spaces [5,40,41], but the complete description of the spectral properties is found only for some special classes of operators, in particular, for Toeplitz operators with generating symbols invariant under some group actions, see Vasilevski [39], Grudsky, Quiroga-Barranco, and Vasilevski [11], Dawson, Ólafsson, and Quiroga-Barranco [8]. The simplest class of this type consists of Toeplitz operators with bounded radial generating symbols.…”
Section: Introduction Backgroundmentioning
confidence: 99%